Approximate Generalized Cubic *-Derivations - Heejeong Koh; Dongseung Kang (Journal of Function Spaces)
We will show the general solution of the functional equation f(ax+by)+f(ax-by) = ab2[f(x+y)+f(x-y)]+2a(a2-b2)f(x) and investigate the stability of cubic *-derivations associated with the given functional equation on Banach *-algebras.